Development of the Gurukula Education System in India - Vinod Kumar Shanwal (Journal of Education and Teacher Training Innovation, 2023)
The traditional Gurukul system is not widely practiced in contemporary society, however This system continues to inspire modern education systems due to its focus on holistic development and unique features . The Gurukul system has influence modern Indian education in a number of method . Objective from study This  ie For know development as well as The relevance of the gurukul education system in schools in India in this modern era . Method research used _ ie method integrated research _ studies References with studies field . Study This conducted at 5 schools Dayanand Anglo-Vedic Public School, Ananda Marga Gurukula , Bhaktivedanta Gurukula and International School, Gurukul Kishangarh Ghasera and Gurukul Kaalba with amount sample as many as 10 teachers and 5 heads school . Tool data collection using interview instruments For studies field . Deep data analysis techniques study This that is using technique descriptive . Research result This showing that Gurukul system incorporates spirituality to in education with emphasize importance moral values , discipline self , and spiritual development of students below guidance a teacher or guru. The Gurukul system teaches discipline good self and humanism _ through various aspect approach his education like  Student living in the Gurukul, the home of the guru or 'Acharya', is possible they Study from Teacher's example and values . Gurukul system in ancient India teach various eye lessons , incl astronomy , medicine , philosophy , science politics , economics , religion, yoga, education physical , studies defense , Vedic literature , Sanskrit , mathematics , and the sciences other Indian traditional . Discussion group play role important in Gurukul system , because discussion group is means for student For Study One each other and get involved in thinking critical , knowledge practical , and understanding analytical . System Gurukul education in ancient India offer a number of benefits , some of them Still relevant until moment This . This including Holistic Development , Emphasis on Knowledge Practical , Competition Healthy and Reducing Stress , Relationships Student -Teacher, Activities extracurricular , Development personality and Spiritual and Ethical Training . Implications from study This is that the education system Gurukula Still relevant used at the time this is necessary done adjustments and refreshing to the education system This still relevant and appropriate with development era and combined with IT will more optimal and newest